Management of the enterprise wage fund in the context of the EAF Model - Renkas, Iryna; Rosa, Kacper (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
This study aims to develop and verify in empirical applications an economic model for determining the real level of employee remuneration, human capital utilization, and managerial efficiency within enterprises. Amidst ongoing debates concerning wage structures and compensation systems, this research introduces the Economic Activity Function (EAF) as a tool for analyzing labor productivity and wage distribution. A mixed-methods approach was employed, combining a literature review to establish the role of the economic constant a = 0.08 [1/year] in compensation analysis with an empirical case study of Komfort-Eko Ltd. Utilizing financial statement data, key indicators—including the Management Index (M) and the Labour Productivity Index (Q)—were calculated to assess wage fund allocation efficiency. Findings reveal that the EAF framework enables the estimation of crucial managerial indicators, serving as a valuable instrument for evaluating corporate performance and optimizing remuneration structures. By forecasting labor productivity for subsequent periods, businesses can predict remuneration levels, including bonus allocations, thereby enhancing financial planning and employee motivation. The implications of this study extend to policymakers and business leaders, providing a robust analytical framework for evaluating management quality, labor productivity, and remuneration fairness. The predictive capabilities of the EAF model facilitate financial scenario planning and decision-making, ultimately contributing to a more structured and data-driven approach to corporate wage management.

Niniejsze badanie ma na celu opracowanie i weryfikację w zastosowaniach empirycznych modelu ekonomicznego umożliwiającego określenie rzeczywistego poziomu wynagrodzeń pracowników, stopnia wykorzystania kapitału ludzkiego oraz efektywności zarządzania w przedsiębiorstwach. W kontekście toczącej się debaty na temat struktury wynagrodzeń i systemów płacowych, wprowadzone zostaje pojęcie Funkcji Aktywności Ekonomicznej (EAF) jako narzędzia analizy wydajności pracy i dystrybucji wynagrodzeń. W badaniu zastosowano metodologię mieszaną, obejmującą przegląd literatury w celu ustalenia roli stałej ekonomicznej a = 0,08 [1/rok] w analizie systemu wynagrodzeń oraz studium przypadku przedsiębiorstwa Komfort-Eko Sp. z o.o. Na podstawie danych ze sprawozdań finansowych obliczono kluczowe wskaźniki, w tym Wskaźnik Zarządzania (M) i Wskaźnik Wydajności Pracy (Q), celem oceny efektywności alokacji funduszu płac. Wyniki badań wskazują, że model EAF umożliwia oszacowanie kluczowych wskaźników zarządczych, stanowiąc istotne narzędzie oceny efektywności przedsiębiorstwa oraz optymalizacji struktury wynagrodzeń. Prognozowanie poziomu wydajności pracy na kolejne okresy pozwala na przewidywanie wysokości wynagrodzeń, w tym funduszu premiowego, co usprawnia planowanie finansowe i motywację pracowników. Implikacje badawcze obejmują zarówno decydentów politycznych, jak i liderów biznesu, dostarczając im rzetelnego narzędzia analitycznego do oceny jakości zarządzania, produktywności pracy oraz sprawiedliwości systemu wynagrodzeń. Możliwości prognostyczne modelu EAF ułatwiają planowanie scenariuszowe oraz podejmowanie decyzji strategicznych, przyczyniając się do bardziej ustrukturyzowanego i opartego na danych podejścia do zarządzania płacami w przedsiębiorstwach.
Zarządzanie zakładowym funduszem płac w kontekście modelu EAF
Keywords: EAF model; Management Index; Labor Productivity Index; wage fund; Model EAF; wskaźnik zarządzania; wskaźnik produktywności pracy; fundusz płac